High-Resolution EEG Amplifiers Are Feasible for Electrocochleography Without Time Restriction - Florian Josef Schertenleib; Sabine Hochmuth; Jana Annina Müller; Pascale Sandmann; Andreas Radeloff (Audiology Research)
Objectives: The gold standard for electrocochleography (ECochG) is using dedicated recording devices for auditory evoked potentials. However, these have a very limited time window for recording. The aim of this study is to evaluate EEG amplifiers for ECochG, in particular for recording cochlear microphonics (CMs) without time restriction. Methods: Three high-resolution EEG amplifiers and different types of electrodes were analyzed and compared with a clinical system for recording auditory evoked potentials. For this, CMs were recorded after stimulation with various stimuli in a dummy and in human subjects. In the latter, recordings were made from the tympanic membrane and, during otosurgical procedures, from the promontory. Our evaluation focused on comparing signal amplifiers and electrode types, considering the signal-to-noise ratio, recording characteristics, and measurement reliability. Results: Using a dummy model, we observed significant differences among devices, electrode types, and stimulus frequencies. These findings were subsequently confirmed in human participant measurements. Nevertheless, EEG amplifiers proved to be feasible for ECochG recordings and offered a recording fidelity comparable to proprietary clinical methods. Importantly, with EEG amplifiers, we were able to record cochlear potentials in response to speech stimuli, revealing a strong correlation (r = 0.78) between recorded signals and the input stimulus. Conclusions: Our findings indicate that high resolution EEG amplifiers are suitable for recording cochlear potentials, in particular, CMs. This allows for evaluating cochlear signals in response to extended stimuli, in particular, speech stimuli.